The future of the global noncommunicable disease agenda after Covid-19. (September 2021) - Herrick, Clare; Reubi, David
Highlights: The burden of noncommunicable diseases (NCDs) across the world is known, but concrete action is lacking. Covid-19 has made the risks of and vulnerabilities from NCDs more visible. The future of the global NCD agenda is uncertain, but needs to be included in pandemic preparedness.